Estudo fitoquímico dos galhos da espécie Rhamnidium elaeocarpum reissek (Rhamnaceae) e das sementes de Xylopia aromatica (Lam.) Mart. e atividades biológicas - Sousa, Mayara Conceição (2021)
The species Rhamnidium elaeocarpum (Rhamnaceae), is popularly known as cabriteiro, Saguaraji, Bosta de cabrito, Cabrito ou Cafezinho, is distributed from Peru to eastern Brazil and Argentina, and in Brazil it can be found in all regions of the country. The species Xylopia aromatica (Annonaceae) is popularly known as Pindaíba, Pimenta de Macaco, Embira e Banana de Macaco, in Brazil, it is typical of the cerrado but can be found in the five Brazilian regions. Both species are widely used in folk medicine to treat fevers, flu, parasitic diseases, to reduce itching of the gums at the beginning of teething and for stomach pain. This work describes the isolation and identification of secondary metabolites in the species Rhamnidium elaeocarpum and Xylopia aromatica, in addition to verifying the antioxidant activity by the DPPH method in extracting fractions and isolated substances of the latter species. From the chloroform fraction of the branches of Rhamnidium elaeocarpum, the anthraquinone chrysophanol (2) and the mixture of β-sitosterol (30) and stigmasterol (31) steroids were isolated. From the ethyl acetate fraction of Xylopia aromatica seeds, the phenolic amide N-trans-caffeoyltyramine (32) and the lignamide cannabisine B were isolated. The crude methanol extract (EBMeOHx), the ethyl acetate (FAcOEtx), chloroformic (FCHCl3x) fractions and the substance N-transcaffeoyltyramine (32) from the seeds of Xylopia aromatica, were submitted to antioxidant analysis by the DPPH method. EBMeOHx showed a result superior to the other fractions, reaching its maximum DPPH free radical capture potential at approximately 50 µg/mL. FAcOEtx presented a percentage of 85% at the concentration of 50 µg/mL and 90% at the concentration of 100 µg/mL. An expressive result was found at the concentration of 50 µg/mL (85%), however the values displayed at the concentration of 100 µg/mL (90%) were more significant. FCHCl3x showed a significant difference between concentrations of 50 and 100 µg/mL, approximately 65 and 80% respectively. N-trans-caffeoyltyramine (32) had the lowest percentage among the others, 60% for the concentration of 50 µg/mL and 65% for 100 µg/mL.